2022
DOI: 10.23886/ejki.10.96.162-7
|View full text |Cite
|
Sign up to set email alerts
|

Kontrasepsi Hormonal Berbasis Progestin pada Perempuan dengan Riwayat Tumor Jinak Payudara

Abstract: Seorang perempuan berusia 38 tahun dengan G5P1A3 (AH1) dan riwayat abortus habitualis, memiliki riwayat tumor jinak payudara 12 tahun lalu dan sudah dilakukan eksisi dengan hasil patologi dinyatakan jinak. Saat ingin menggunakan kontrasepsi hormonal, tenaga kesehatan menolak karena pasien memiliki riwayat tumor jinak payudara. Evidence based case report ini bertujuan untuk menelaah pengaruh kontrasepsi hormonal berbasis progestin pada perempuan dengan riwayat tumor payudara. Dilakukan pencarian melalui Pubmed®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Women who use oral contraceptives today have a quarter-fold greater risk than women who stopped using them 10 years ago, but the increased risk is statistically insignificant. 18 Previous research suggested that using hormonal contraceptives for > 5 years could increase the risk of breast cancer by 1.52 times. It can occur due to the accumulation of the hormone estrogen in the body.…”
Section: History Of Use Of Contraception Pills With Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Women who use oral contraceptives today have a quarter-fold greater risk than women who stopped using them 10 years ago, but the increased risk is statistically insignificant. 18 Previous research suggested that using hormonal contraceptives for > 5 years could increase the risk of breast cancer by 1.52 times. It can occur due to the accumulation of the hormone estrogen in the body.…”
Section: History Of Use Of Contraception Pills With Breast Cancermentioning
confidence: 99%
“…The results differ from the study of Mariahadi (2017) and Madjid et al, (2022), which stated that there was no significant relationship between the history of hormonal CB use and the incidence of breast cancer. [15][16][17][18] The results of Tambunan's (2017) and Sari's (2017) research showed that there is a link between the level of knowledge and early detection of breast cancer. However, unlike the results of Immawati and Utami (2017) and Toki and Kelen (2019) studies, there is no significant relationship between the level of knowledge and early detection of breast cancer.…”
Section: Introductionmentioning
confidence: 99%